Identification of nonparametric simultaneous equations models with a residual index structure - Steven Berry; Philip Haile (Centre for Microdata Methods and Practice (cemmap), 2015)
We present new results on the identifiability of a class of nonseparable nonparametric simultaneous equations models introduced by Matzkin (2008). These models combine exclusion restrictions with a requirement that each structural error enter through a "residual index". Our identification results encompass a variety of special cases allowing tradeoffs between the exogenous variation required of instruments and restrictions on the joint density of structural errors. Among these special cases are results avoiding any density restriction and results allowing instruments with arbitrarily small support.
Keywords: 330